The Effect of Cutting Fluids and Cutting Speeds to The Vibrations of Milling CNC Machine - A Muhammad Fuad Nur Rochim; Indri Yaningsih; Heru Sukanto (Mekanika: Majalah Ilmiah Mekanika, 2017)
Vibration that occur in machining process is forced vibration. This vibration caused by external force excitation. External force that cause vibration in machining process is cutting force. This research was aims to determine the effect of cutting fluids and cutting speeds to vibration in milling process. The specimens were made using a cutting process type face milling, profile milling, pocket milling, and slot milling. Cutting speeds was variated at 62.83 m/min; 110 m/min; 157.14 m/min; 188.5 m/min. Vibration testing was done using the accelerometer sensor. Vibration response taken is the amplitude. The results show any type of cutting process has a different amplitude. Face milling has the smallest amplitude while slot milling has the biggest one. At cutting speeds parameter, the faster of cutting speeds the smaller of the amplitude. The use of cutting fluids can reduce the friction value between cutting tool and workpiece so that the cutting force will decrease. The use of cutting fluids causing the smaller the cutting force. The increase of the cutting force will cause greater vibration